Measuring nonverbal immediacy across learning modes: psychometric properties of the 12-item VINI Scale (virtual and interpersonal nonverbal immediacy) - Gordon, Aviva; Cole, Matthew L. (Frontiers in Education, 2026)
Nonverbal immediacy, the set of communicative behaviors that reduce psychological distance between individuals, has been a cornerstone of instructional communication research for over half a century. However, the proliferation of online, hybrid, and blended learning environments has challenged traditional immediacy measurement, creating a need for a modernized tool. This study reports on the development and psychometric validation of the Virtual and Interpersonal Nonverbal Immediacy (VINI) Scale, a 12-item self-report instrument designed to measure instructor immediacy across contemporary learning modalities. The VINI Scale comprises two distinct but correlated factors: Physiological Immediacy (gestures, eye contact, vocal expressiveness, animated movement, body orientation, smiles) and Virtual Immediacy (emoji use, colorful visuals, embedded video, varied typography, interactive technology, collaborative tools). Virtual Immediacy is operationalized as technologically-mediated, design-based behaviors enacted in digital environments—particularly asynchronous online contexts—that signal instructor presence and engagement. Data were collected through a dual-framework design, capturing both learner observations of instructor behaviors (VINI-O, N = 447) and learner preferences for those behaviors (VINI-P, N = 295). Confirmatory factor analysis supported a first-order, two-factor model as optimal across both samples. Multi-group analyses established configural invariance across participant gender, instructor gender, and instructional method comparisons, with VINI-P achieving scalar invariance across instructional method, enabling meaningful comparisons between face-to-face and online contexts. The VINI Scale offers researchers a reliable and valid instrument to investigate modernized nonverbal immediacy and provides practitioners across educational, corporate, and health contexts with an evidence-based framework to enhance social presence and engagement in any learning environment.